Harmonic Reduction Using THIPWM Switching Technique with Type-2 Fuzzy on 3-Phase Motor - Murdianto, Farid Dwi; Wahdjono, Endro; Ramadani, Fahri (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2023)
The development of the increasingly advanced industrial world has increased the need and use of electric motors for various purposes. In the industrial world, many electric motors are found as a driving device to drive various equipment needed, including a three-phase induction motor. The induction motor is expected to operate normally by the desired working characteristics. But it is undeniable that in its use, there are disturbances that can cause damage to the work system of the Induction motor, one of which is harmonic interference. The influence of harmonics on the induction motor causes copper and core losses which will reduce the efficiency motor and cause harmonic torque along with fundamental torque to produce vibration and noise, which considerably affect the operation three-phase induction motor. In this study, a 3-phase inverter was used with the Third Harmonic Injection pulse width modulation (THIPWM) method, with the use THIPWM Switching Method expected to increase the output voltage three-phase inverter and reduce the harmonics caused by the three-phase induction motor. In optimizing a 3-phase induction motor's speed regulation, scalar control or voltage/frequency (v/f) regulation is used. With the use THIPWM switching on this three-phase inverter, it is evident from simulation results that the harmonic value of THDV is 55.62%. THDI is 19.04%, as well the acceleration 3-phase induction motor with a rise time value of 48.547ms with steady-state error of 0.08% at set point 1200 rpm and with rise time value of 52.938ms with steady-state error 0% at set point 1000 rpm.